Genetic Evidence of a Long-Range RNA-RNA Interaction between the Genomic 5′ Untranslated Region and the Nonstructural Protein 1 Coding Region in Murine and Bovine Coronaviruses - Guan, Bo-Jhih (American Society for Microbiology, 2012)
Higher-order RNA structures in the 5′ untranslated regions (UTRs) of the mouse hepatitis coronavirus (MHV) and bovine coronavirus (BCoV), separate species in the betacoronavirus genus, appear to be largely conserved despite an ∼36% nucleotide sequence divergence. In a previous study, each of three 5′-end-proximal cis-acting stem-loop domains in the BCoV genome, I/II, III, and IV, yielded near-wild-type (wt) MHV phenotypes when used by reverse genetics to replace its counterpart in the MHV genome. Replacement with the BCoV 32-nucleotide (nt) inter-stem-loop fourth domain between stem-loops III and IV, however, required blind cell passaging for virus recovery. Here, we describe suppressor mutations within the transplanted BCoV 32-nt domain that along with appearance of potential base pairings identify an RNA-RNA interaction between this domain and a 32-nt region ∼200 nt downstream within the nonstructural protein 1 (Nsp1)-coding region. Mfold and phylogenetic covariation patterns among similarly grouped betacoronaviruses support this interaction, as does cotransplantation of the BCoV 5′ UTR and its downstream base-pairing domain. Interestingly, cotransplantation of the BCoV 5′ UTR and BCoV Nsp1 coding region directly yielded an MHV wt-like phenotype, which demonstrates a cognate interaction between these two BCoV regions, which in the MHV genome act in a fully interspecies-compliant manner. Surprisingly, the 30-nt inter-stem-loop domain in the MHV genome can be deleted and viral progeny, although debilitated, are still produced. These results together identify a previously undescribed long-range RNA-RNA interaction between the 5′ UTR and Nsp1 coding region in MHV-like and BCoV-like betacoronaviruses that is cis acting for viral fitness but is not absolutely required for viral replication in cell culture.